((x2 - x) / (x2 - 2x + 1 )) . ((x2 - 1) / (5x + 5)) gostaria de saber como se faz essa expressão.
Respostas
respondido por:
0
Boa noite Baltha
((x² - x)/(x² - 2x + 1)) * ((x² - 1)/(5x + 5))
você pode fazer assim
x² - x = x*(x - 1)
x² - 2x + 1 = (x - 1)²
x² - 1 = (x + 1)*(x - 1)
5x + 5 = 5*(x + 1)
agora é mais simples
x*(x - 1)/(x - 1)² * (x + 1)*(x - 1)/(5*(x + 1))
x*(x - 1)²/(x - 1)² * (x + 1)/(x + 1) / 5)
E = x/5
((x² - x)/(x² - 2x + 1)) * ((x² - 1)/(5x + 5))
você pode fazer assim
x² - x = x*(x - 1)
x² - 2x + 1 = (x - 1)²
x² - 1 = (x + 1)*(x - 1)
5x + 5 = 5*(x + 1)
agora é mais simples
x*(x - 1)/(x - 1)² * (x + 1)*(x - 1)/(5*(x + 1))
x*(x - 1)²/(x - 1)² * (x + 1)/(x + 1) / 5)
E = x/5
respondido por:
0
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás